The Transformation of English Teaching Models and the Development of Intelligent Learning Environments in Higher Education Enabled by Mobile Technology - Mi, Haimin; Guo, Sheng (International Journal of Interactive Mobile Technologies (iJIM), 2025)
With the rapid advancement of mobile technology, unprecedented opportunities for transformation have emerged in English teaching within higher education. The widespread adoption of mobile devices has extended the temporal and spatial dimensions of learning while significantly enriching the forms and content of teaching interaction. This evolution has driven a pedagogical shift from closed, linear models toward open, dynamic frameworks. Within this context, in-depth research on teaching interaction relationships under mobile-interactive environments has become critical for enhancing both teaching effectiveness and learner experience. Although previous studies have explored the design and implementation of mobile learning platforms, most have remained at a functional level, lacking quantitative analysis and structural identification of teaching interaction. Moreover, interaction data have primarily been processed using static methods, limiting the ability to dynamically capture authentic patterns and evolving trends in learner interaction. Therefore, a systematic research framework is urgently required—one capable of accurately identifying interaction relationships while translating analytical results into actionable strategies for pedagogical optimization and learning environment development. To address these needs, this study undertakes two core objectives: first, to identify teaching interaction relationships in mobile-interactive contexts by analyzing the structure, characteristics, and evolution of teacher-student and student-student interactions; second, to optimize English teaching models based on these findings and to construct an intelligent, personalized learning environment system. By leveraging data mining of mobile interaction relationships, a visualized and structured feedback mechanism was proposed for instructional practice, thereby promoting the development of English teaching in higher education toward a more intelligent, efficient, and interactive paradigm.